No Pharmacokinetic Interactions Between Elbasvir or Grazoprevir and Buprenorphine/Naloxone in Healthy Participants and Participants Receiving Stable Opioid Agonist Therapy. Issue 6 (24th July 2018) - Feng, Hwa‐Ping; Guo, Zifang; Caro, Luzelena; Marshall, William L.; Liu, Fang; Panebianco, Deborah; Vaddady, Pavan; Barbour, April; Reitmann, Christina; Jumes, Patricia; Gilmartin, Jocelyn; Wolford, Dennis; et al.
Abstract: The aims of these phase I trials were to evaluate the pharmacokinetic interaction between elbasvir (EBR) or grazoprevir (GZR) and buprenorphine/naloxone (BUP/NAL). Trial 1 was a single‐dose trial in healthy participants. Trial 2 was a multiple‐dose trial in participants on BUP/NAL maintenance therapy. Coadministration of EBR or GZR with BUP/NAL had minimal effect on the pharmacokinetics of BUP/NAL, EBR, and GZR. The geometric mean ratios (GMRs (90% CI)) for BUP, norbuprenorphine, and NAL AUC0‐∞ were 0.98 (0.89–1.08), 0.97 (0.86–1.09), and 0.88 (0.78–1.00) in the presence/absence of EBR; 0.98 (0.81–1.19), 1.13 (0.97–1.32), and 1.10 (0.82–1.47) in the presence/absence of GZR. The GMRs (90% CI) for EBR and GZR AUC0‐∞ in the absence/presence of BUP/NAL were 1.22 (0.98–1.52) and 0.86 (0.63–1.18). In conclusion, no dose adjustment for BUP/NAL, EBR, or GZR is required for patients with HCV infection receiving EBR/GZR and BUP/NAL maintenance therapy .